Entropy generation analysis in MHD hybrid nanofluid flow over a rotating surface for sustainable energy applications - N. Rangra; M.S. Arslan; Z. Abbas; M.Y. Rafiq (Results in Engineering)
This study presents a comprehensive analysis of entropy generation and heat transfer characteristics in the magnetohydrodynamic (MHD) flow of an electrically conducting Ag-Al₂O₃/water hybrid nanofluid over a vertically rotating cone. Such configurations are relevant in various advanced engineering systems including solar thermal collectors, cooling devices, and aerospace components. The model accounts for the effects of viscous dissipation, thermal radiation, Joule heating, and mixed convection, under two thermal boundary conditions: prescribed surface temperature and prescribed surface heat flux. The governing nonlinear partial differential equations are transformed into ordinary differential equations using similarity transformations and solved numerically via MATLAB’s bvp4c solver. The results reveal that silver nanoparticles significantly enhance thermal performance compared to aluminum oxide. Entropy generation increases with Brinkman number and radiation parameter, while the Bejan number decreases, indicating stronger thermal irreversibility. The findings offer valuable insights into optimizing energy systems for improved thermal efficiency and reduced entropy production, particularly in the context of renewable energy applications.